Effect of slightly acidic electrolyzed water in drinking water on the intestinal morphology and gut microbiota in early weaned piglets - Shi, Zhifang; Xi, Lei; Wei, Ruiting; Shi, Zhengyang; Xu, Zike; Gao, Shuilin; Liang, Xiaoxuan; Zhang, Yifang; Ye, Zhangying; Cheng, Pu (Frontiers in Animal Science, 2025)
IntroductionThis study investigated the effects of slightly acidic electrolyzed water (SAEW) on the gut morphology and microbiota structure in early weaned piglets.MethodsA total of 144 healthy Large White × Landrace × Duroc weaned piglets (21 days old, sex in half, each weighing 7.0 ± 0.5 kg) were randomly assigned into three groups. Each group included four replicates, with each replicate comprising 12 piglets. The weaned piglets in the control (CON) group drank only disinfected tap water. Those in experimental groups I and II were given SAEW with available chlorine concentrations (ACCs) of 0.3 and 0.6 mg/L, respectively. The formal experimental period was 15 days.ResultsThe results showed that the weight and the length of the intestines of the piglets in the SAEW I and II groups significantly increased compared with those in the CON group. In the jejunum, the villus height of the SAEW II group significantly increased by 13.1% compared with the CON group (p < 0.05). In the ileum, the villus heights of the SAEW I and II groups significantly increased compared with the CON group (p < 0.05). The villus height/crypt depth ratio of the two experimental groups significantly increased compared with that of the CON group (p < 0.05). No significant changes were observed in the gut microbial diversity. However, the relative abundance (RA) of Bacteroidetes, Proteobacteria, and Actinobacteria increased compared with the CON group (p < 0.05). The RA of Firmicutes in the duodenum, jejunum, ileum, and cecum of piglets significantly decreased in the SAEW I and II groups. At the genus level, the RA of Lactobacillus decreased (p < 0.05), while that of Streptococcus, Prevotella, and Eubacterium increased (p < 0.05).DiscussionIn conclusion, drinking SAEW significantly improves the intestinal development and the morphological structure of piglets and significantly promotes the colonization of the Streptococcus, Prevotella, and Eubacterium flora in the intestinal tract, but reduces the abundance of Lactobacillus in the small intestine. This might be related to the alteration of the intestinal pH value by SAEW. The application effects of more SAEW concentrations require further experimental research.